PENGGUNAAN BAHAN AJAR BERBASIS HIGHER ORDER THINKING SKLILLS (HOTS) DALAM MATA KULIAH PENGEMBANGANAN PEMBELAJARAN IPA SD - Utaminingsih, Retno; Rahayu, Ayu (Universitas Sarjanawiyata Tamansiswa, 2021)
Guidelines for organizing learning in tertiary institutions in online courses are developed based on learning process planning documents, one of which uses teaching materials. Good teaching materials are teaching materials that meet qualification standards. Teaching materials have an important position in learning and have an effective influence on increasing student activity and learning outcomes in the lecture process. Because learning in tertiary institutions should be able to involve students in higher-order thinking activities, it is better if in the lecture process in higher education learning materials used are HOTS (Higher order thinking skills) based teaching materials so that in their activities they can involve students to be involved. in higher-order thinking activities.